Parametric modeling and comparative finite element analysis of spiral triangular strand and simple straight strand. (December 2015) - Chen, Yuanpei; Meng, Fanming; Gong, Xiansheng
Highlights: A new parametric geometric model of spiral triangular strand is developed. Both strands show elasto-plastic behaviors under axial tensile and torsional loads. Triangular strand has smaller tensile and torsional stiffness than simple strand. Discontinuous contact of triangular strand cause nonuniform stress distribution. Abstract: Spiral triangular strand (STS) and simple straight strand (SSS) are widely used in practical applications, but comparative analyses aimed for a better comprehension of the service behavior are seldom conducted due to the complex geometric configuration of STS. In the present study, a new parametric geometric model of STS, considering the effect of lay angle on the wire cross section, is proposed by means of parametric equations and Pro/Engineer software. Full 3D finite element (FE) models of the STS and SSS are developed with ANSYS software. Under axial tensile and torsional loads, the behaviors of the STS and SSS with the same lay angle and total wire sectional area are comparatively studied, and the comparison are conducted at different lay angles and outer wire diameters. The results of FE analyses show that nonlinear overall behaviors happen to the both kinds of strands. The STS results in smaller axial force and torque, but severer plastic deformation and von Mises stress than the SSS, and the discrepancies increase with increasing lay angle and outer wire diameter. The discontinuous contact lines of the STS lead to the nonuniform distribution of von Mises stress and significant contact pressure.